Quadratic Boost DC–DC Converters Capable of Being Extended to Improved Topologies - Mohammadfazel Dehghan; Hossein Gholizadeh; Reza Sharifi Shahrivar; Saeed Amini; Hani Vahedi (IEEE Access)
Luo converters represent the most extensive family of non-isolated DC-DC converters, yet achieving high voltage gain in these topologies often compromises simplicity. This study introduces a novel family of quadratic boost converters that address this challenge by combining six key features: 1) continuous input current, 2) reduced component count, 3) optimized voltage/current stress on semiconductors, 4) higher voltage gain than conventional designs, 5) high efficiency across a wide duty-cycle range, and 6) topological extensibility comparable to Luo converters. The proposed topologies are analyzed in both ideal and non-ideal operating modes, with derived expressions for voltage gain and efficiency sensitivity. Design requirements are detailed for continuous conduction mode (CCM), complemented by small-signal analysis and compensator design for the primary family members. Experimental results validate the theoretical models, demonstrating the converters’ performance and robustness. Additionally, voltage gain tests for extended topologies confirm their adherence to theoretical predictions. The proposed family offers a streamlined, high-performance alternative to existing Luo converters, with potential applications in high-gain, non-isolated power conversion systems.